2021
DOI: 10.1007/s00330-021-07764-6
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced pancreatic carcinoma with jaundice: the benefit of a sequential treatment with stenting followed by CT-guided 125I seeds implantation

Abstract: Objectives To evaluate the role of sequential therapy with percutaneous biliary stenting and CT-guided iodine-125 seed implantation for locally advanced pancreatic carcinoma with concomitant obstructive jaundice. Methods Between January 2016 and December 2018, 42 patients diagnosed with locally advanced pancreatic carcinoma with concomitant obstructive jaundice were enrolled retrospectively. All patients received biliary stenting via percutaneous transhepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…All patients underwent percutaneous biliary stent implantation, and the treatment group received CT-guided implantation 125 The results showed that the median OS of the treatment group was 11.67 months, while that of the control group was 9.40 months. The effective rate (complete remission + partial remission) of the treatment group was 72.7%, while that of the control group was only 30% at 6 months follow-up, and no serious complications occurred in all patients [14]. Li Hongwei et al observed 90 cases 125 I No serious complications occurred in the pancreatic cancer patients after particle implantation, including 31 cases with complete remission of cancer pain, 17 cases with partial remission, and 14 cases with ineffective treatment.…”
Section: I Particle Brachytherapymentioning
confidence: 81%
See 1 more Smart Citation
“…All patients underwent percutaneous biliary stent implantation, and the treatment group received CT-guided implantation 125 The results showed that the median OS of the treatment group was 11.67 months, while that of the control group was 9.40 months. The effective rate (complete remission + partial remission) of the treatment group was 72.7%, while that of the control group was only 30% at 6 months follow-up, and no serious complications occurred in all patients [14]. Li Hongwei et al observed 90 cases 125 I No serious complications occurred in the pancreatic cancer patients after particle implantation, including 31 cases with complete remission of cancer pain, 17 cases with partial remission, and 14 cases with ineffective treatment.…”
Section: I Particle Brachytherapymentioning
confidence: 81%
“…CT should be reexamined immediately after the operation and introduced into the TPS treatment system to observe the distribution of particles and check the number of particles, and evaluate the implementation of the plan. If there is an obvious dose deficiency area, namely the cold area, replantation can be carried out [13][14][15][16]. Multiple center studies showed cT-guided radioactivity 125 I Particle implantation in unresectable pancreatic cancer has a significant short-term efficacy, which can effectively control tumor cell growth, reduce tumor volume, relieve pain and improve quality of life.…”
Section: I Particle Brachytherapymentioning
confidence: 99%
“…The overall survival of these 21 patients was 5.2-23.3 months, which was similar to that of the present study. Chen et al [21] selected 42 LAPHC patients with obstructive jaundice, and twenty-two patients underwent CT-guided 125 I seed placement after biliary stenting via percutaneous transhepatic biliary drainage (PTBD). The overall positive response rate at 6 months after treatment was 72.7% (16/22) and 30% (6/20) in patients who received and did not receive particle implantation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…If there is still a cold radiant zone in the lesion, stage II 125 I seed implantation can be performed without complications after two weeks. 40 , 41 , 42 Postoperative observation and treatment The patient should fast for 6 ​hours postoperatively. Observe the general vital signs of the patient after the operation, including signs of abdominal pain, abdominal distension, and stool color.…”
Section: Percutaneous 125 I Seed Implantationmentioning
confidence: 99%
“…If there is still a cold radiant zone in the lesion, stage II 125 I seed implantation can be performed without complications after two weeks. 40 , 41 , 42 …”
Section: Percutaneous 125 I Seed Implantationmentioning
confidence: 99%